2021
DOI: 10.3390/s21041199
|View full text |Cite
|
Sign up to set email alerts
|

Hand Motion Capture from a 3D Leap Motion Controller for a Musculoskeletal Dynamic Simulation

Abstract: The AnyBody Modeling System™ (AMS) is a musculoskeletal software simulation solution using inverse dynamics analysis. It enables the determination of muscle and joint forces for a given bodily motion. The recording of the individual movement and the transfer into the AMS is a complex and protracted process. Researches indicated that the contactless, visual Leap Motion Controller (LMC) provides clinically meaningful motion data for hand tracking. Therefore, the aim of this study was to integrate the LMC hand mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…It can be seen from the definition of progress label that progress label is related to the action category. A network can only learn the progress label information of one kind of action [27]. erefore, it is necessary to train the progress label prediction network belonging to each kind of action k. e training data are the video frame of the action instance belonging to the k-th progressive action in the training video sample.…”
Section: Establishment Of the Arm Motion Analysis Model Based On Deepmentioning
confidence: 99%
“…It can be seen from the definition of progress label that progress label is related to the action category. A network can only learn the progress label information of one kind of action [27]. erefore, it is necessary to train the progress label prediction network belonging to each kind of action k. e training data are the video frame of the action instance belonging to the k-th progressive action in the training video sample.…”
Section: Establishment Of the Arm Motion Analysis Model Based On Deepmentioning
confidence: 99%
“…Chophuk et al [47] suggested small error angles in fingers using LMC to recognize real finger movement. Recently, Fonk et al [48] reported that the LMC is able to provide a correct estimation of the orientation of the hand bones and joint positions to be reproduced with precision in software with biomechanical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Joint Angle (JA) [ 64 , 65 ]: This feature represents the angle between every two adjacent bones at the interphalangeal and metacarpophalangeal joints. For example, for the distal interphalangeal joint, is derived by Equation ( 6 ).…”
Section: Methodsmentioning
confidence: 99%